2021
DOI: 10.3390/ijerph18168633
|View full text |Cite
|
Sign up to set email alerts
|

Association of Family History and Life Habits in the Development of Colorectal Cancer: A Matched Case-Control Study in Mexico

Abstract: Colorectal cancer (CRC) is one of the most frequently diagnosed cancers and, as such, is important for public health. The increased incidence of this neoplasm is attributed to non-modifiable controls such as family history and modifiable variable behavioral risk factors involved in lifestyle like diets in Mexico. The presence of these factors is unknown. Therefore, the aim of this study was to evaluate family history and lifestyle factors associated with developing colorectal cancer in a Mexican population. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Our study revealed a robust correlation between a positive family history of CRC and an increased risk of CRC within the EMRO region. A study conducted by Ramírez-Díaz further confirmed the crucial role of family history as a significant factor influencing the occurrence of CRC 47 . These findings may be attributed to shared or similar gene sequences among family members, which could accelerate the mechanisms of CRC.…”
Section: Discussionmentioning
confidence: 84%
“…Our study revealed a robust correlation between a positive family history of CRC and an increased risk of CRC within the EMRO region. A study conducted by Ramírez-Díaz further confirmed the crucial role of family history as a significant factor influencing the occurrence of CRC 47 . These findings may be attributed to shared or similar gene sequences among family members, which could accelerate the mechanisms of CRC.…”
Section: Discussionmentioning
confidence: 84%